Aluminum-plated steel plate for hot stamping

By setting a surface treatment film of oxides or fluorides of high carbon concentrations of compound A and metal element M on the aluminum-plated steel plate, the problem of insufficient heating speed due to long heating time and organic matter in the prior art is solved, and a more efficient hot stamping production process is achieved.

CN119768555APending Publication Date: 2025-04-04NIPPON STEEL CORPORATION
View PDF 4 Cites 0 Cited by

Patent Information

Application Number
CN202380061579.X
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Priority Date
2022-08-29
Filing Date
2023-08-28
Publication Date
2025-04-04

AI Technical Summary

Technical Problem

In the existing hot stamping technology, the steel plate is heated to a desired temperature for a long time, resulting in low productivity. In addition, when organic matter such as carbon pigment is used as films at high temperatures in the aluminum-plated steel plate, these organic matters will disappear at high temperatures, resulting in insufficient heating rate.

Method used

The surface treatment film containing oxides or fluorides of compound A and metal element M with high carbon concentration is provided on the aluminum plating layer of the aluminum-plated steel plate to control the concentration range of metal element M, and to improve the heating rate of the steel plate during heating by adjusting the composition and structure of the film.

Benefits of technology

By increasing the heating speed of the steel plate, shortening the heating time, significantly improving the productivity of the hot stamping members, and maintaining efficient heating performance after the organic matter disappears.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119768555A_ABST
    Figure CN119768555A_ABST
Patent Text Reader

Abstract

This aluminum-plated steel sheet for hot stamping comprises: a base steel sheet; an aluminum plating layer provided on at least one surface of the base steel sheet; and a surface treatment film provided on the aluminum plating layer. The surface treatment film contains: a compound A containing carbon; and a compound B that is an oxide or fluoride of a metal element M and has a rutile-type structure, the carbon concentration of the compound A being 80 mass% or more, and the concentration of the metal element M satisfying formula (1) and formula (2). 1 < = CbM < = 40 formula (1) 1.5 < = CbM / CtM < = 10.0 formula (2), where when the average thickness of the surface treatment film is set as H ([mu] m), CtM in formula (2) is the concentration of the metal element M at a position 0.05 H from the surface of the surface treatment film in terms of mass%, and CbM is the concentration of the metal element M at a position 0.05 H from the surface of the surface treatment film in terms of mass%. CbM in formula (1) and formula (2) is the concentration of the metal element M at a position of 0.95 H from the surface of the surface-treated film in mass%.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to an aluminum-plated steel sheet for hot stamping.

[0002] This application claims priority based on Japanese Patent Application No. 2022-135751 filed in Japan on August 29, 2022, the contents of which are incorporated herein by reference. Background Art

[0003] In recent years, in order to protect the environment and prevent global warming, the demand for suppressing the consumption of chemical fuels has been increasing, and this demand has had an impact on various manufacturing industries. For example, automobiles, which are indispensable as a mobile mechanism in daily life or activities, are no exception, and there is a demand for improved fuel efficiency by reducing the weight of the vehicle body, etc. However, with regard to automobiles, simply reducing the weight of the vehicle body may lead to a reduction in safety such as a reduction in the strength of the vehicle body (for example, a reduction in collision resistance, etc.), which is not preferred in terms of product quality.

[0004] Therefore, when reducing the weight of a vehicle body, it is necessary to appropriately implement it while ensuring safety.

[0005] Most of the structure of a car is made of iron, especially steel plates. Therefore, reducing the weight of the steel plates is effective for lightweighting the car body. In addition, such a demand for reducing the weight of steel plates is not only made in the automobile manufacturing industry, but also in various manufacturing industries. In response to such a demand, if the weight of the steel plates is simply reduced, it is considered to reduce the thickness of the steel plates. However, reducing the thickness of the steel plates will cause the strength of the car body to decrease. Therefore, in recent years, research and development has been carried out on steel plates that can maintain or improve the mechanical strength of the car body composed of steel plates even if they are thinner than the previous steel plates used before by improving the mechanical strength of the steel plates.

[0006] Generally speaking, materials with high mechanical strength tend to have reduced shape freezeability during forming processes such as bending. Therefore, when materials with high mechanical strength are processed into complex shapes, the processing itself becomes difficult. As one of the means to solve such problems related to formability, the so-called "hot stamping method (also called hot pressing method, hot pressing method, high temperature pressing method or die quenching method)" can be cited.

[0007] In the hot stamping method, the material to be formed is heated to a high temperature and transformed (austenized) into a structure called austenite, and the steel plate softened by heating is pressed to form, and then cooled after forming. According to the hot stamping method, since the material is temporarily heated to a high temperature to soften, the material can be easily pressed. Furthermore, the mechanical strength of the material can be improved by the quenching effect brought about by cooling after forming. Therefore, by the hot stamping method, a formed product with good shape freezing and high mechanical strength can be obtained.

[0008] For example, Patent Document 1 discloses a technique for manufacturing a formed product that can be used as an automobile component by processing an alloyed hot-dip galvanized steel sheet by a hot stamping method.

[0009] Patent Documents 2 and 3 disclose a technique for providing an aluminum-plated steel sheet with a film mainly composed of an organic substance such as a carbon pigment, thereby shortening the time required for heating to a desired temperature.

[0010] Prior art literature

[0011] Patent Literature

[0012] Patent Document 1: Japanese Patent Application Publication No. 2003-126921

[0013] Patent Document 2: Japanese Patent Application Publication No. 2011-149084

[0014] Patent Document 3: Japanese Patent Application No. 2017-518438 Summary of the invention

[0015] Problems to be solved by the invention

[0016] Among them, the hot stamping method described in Patent Document 1 requires heating the steel sheet to be processed to 700 to 1000° C. Therefore, time must be ensured to heat the steel sheet to a desired temperature, and improvement in productivity is not sufficient.

[0017] In addition, regarding the aluminum-plated steel sheets described in Patent Documents 2 and 3, since the carbon pigments and the like contained in the film on the steel sheets are all organic substances, when the aluminum-plated steel sheets are heated to a high temperature region of 750° C. or higher, these organic substances disappear. Therefore, regarding the techniques described in Patent Documents 2 and 3, the improvement in productivity is also insufficient.

[0018] The present invention has been made in view of the above-mentioned problems, and an object of the present invention is to provide a steel sheet for hot stamping that can further improve the productivity of hot stamped parts.

[0019] Means for solving problems

[0020] In order to solve the above problems, the inventors of the present invention have conducted in-depth research. As a result, it is recognized that when a hot stamping steel plate is used to manufacture a hot stamping component, if the heating rate when the steel plate is heated to the desired temperature (for example, above the Ac3 point) can be increased, the heating time can be shortened, which can help improve productivity. Specifically, it is recognized that a surface treatment film containing a compound A with a carbon concentration of more than 80% by mass and a compound B having an oxide or fluoride of a metal element M and a rutile structure is provided on the coating, and the concentration range of the metal element M is controlled to a specified range, so that the heating rate can be greatly increased.

[0021] The gist of the present invention completed based on the above findings is as follows.

[0022] [1] An aluminum-plated steel sheet for hot stamping according to one embodiment of the present invention comprises:

[0023] Base steel plate;

[0024] an aluminum plating layer provided on at least one surface of the base steel plate; and

[0025] The surface treatment film is provided on the above-mentioned aluminum coating.

[0026] Wherein, the above-mentioned surface treatment film contains:

[0027] a compound A comprising carbon; and

[0028] A compound B which is an oxide or fluoride of a metal element M and has a rutile structure,

[0029] The carbon concentration of the compound A is 80% by mass or more,

[0030] The concentration of the metal element M satisfies the following formula (1) and the following formula (2).

[0031] 1≤C bM ≤40 Formula (1)

[0032] 1.5≤C bM / C tM ≤10.0 Formula (2)

[0033] When the average thickness of the surface treatment film is set to H (μm), C in the above formula (2) is tM is the concentration of the metal element M at a position 0.05H from the surface of the surface-treated film in mass %,

[0034] In the above formula (1) and (2), C bMIt is the concentration of the metal element M at a position 0.95H from the surface of the surface-treated film in mass %.

[0035] [2] According to the aluminum-plated steel sheet for hot stamping described in [1] above, the content of the compound A at a position 0.90H from the surface of the surface treatment film may be 30% to 80%.

[0036] [3] The aluminum-plated steel sheet for hot stamping according to [1] or [2] above, wherein the compound B may be TiO2.

[0037] Effects of the Invention

[0038] According to the above aspect of the present invention, it is possible to provide a hot stamping steel sheet capable of further improving the productivity of a hot stamped component. BRIEF DESCRIPTION OF THE DRAWINGS

[0039] Figure 1 It is a schematic cross-sectional view of an aluminum-plated steel sheet for hot stamping according to one embodiment of the present invention.

[0040] Figure 2 It is a schematic cross-sectional view of an aluminum-plated steel sheet for hot stamping according to one embodiment of the present invention. DETAILED DESCRIPTION

[0041] Hereinafter, preferred embodiments of the present invention will be described in detail. It should be noted that the present invention is not limited to the configuration disclosed in the present embodiment, and various changes can be made without departing from the scope of the gist of the present invention. In addition, for the numerical value ranges described below, the lower limit and the upper limit are included in the range. Regarding the numerical value expressed as "exceeding" or "lower than", the value is not included in the numerical range.

[0042] (Aluminum-plated steel sheet for hot stamping)

[0043] When the aluminum-plated steel sheet for hot stamping (hereinafter also referred to as "aluminum-plated steel sheet for HS") according to an embodiment of the present invention is used to manufacture a hot stamping component, the heating rate when the aluminum-plated steel sheet for HS is heated can be increased. That is, by using the aluminum-plated steel sheet for HS according to the embodiment of the present invention that can increase the heating rate during heating, the productivity of the hot stamping component can be improved.

[0044] In order to increase the heating rate when heating the aluminum-plated steel sheet for HS, the aluminum-plated steel sheet for hot stamping of the present embodiment has a surface treatment film containing a specified compound on at least one surface of the plated steel sheet with an aluminum coating. By imparting a surface treatment film containing a specified compound to at least one surface of the plated steel sheet provided with an aluminum coating in this way, the heating rate of the obtained aluminum-plated steel sheet for HS when heated can be accelerated. It should be noted that the surface treatment film can be provided on both sides of the plated steel sheet provided with an aluminum coating, or it can be only one surface. In addition, the surface treatment film can be provided on the entire surface of the plated steel sheet provided with an aluminum coating, or it can be a part of the surface. From the viewpoint of further improving the productivity of hot stamping components, the surface treatment film is preferably provided on the entire surface of the plated steel sheet provided with an aluminum coating.

[0045] In the hot stamping aluminum-plated steel sheet of the present embodiment, the type of steel sheet (parent steel sheet) that becomes the base material is not particularly limited. As the parent steel sheet, for example, various hot-rolled steel sheets and cold-rolled steel sheets can be listed. The plated steel sheet constituting the hot stamping aluminum-plated steel sheet of the present embodiment is a plated steel sheet having a coating on at least one surface of such a parent steel sheet. As the plated steel sheet, for example, a steel sheet that has been subjected to hot-dip aluminum plating can be listed. However, as long as it can be applied to hot stamping, the coating of the present embodiment is not limited to the hot-dip aluminum coating layer.

[0046] Conventionally, most of the steel sheets used for automobile frame parts, etc. are hot-rolled steel sheets, cold-rolled steel sheets, or plated steel sheets plated with aluminum, zinc, etc. Since these conventional steel sheets have low emissivity, the heating rate to radiation heating is low.

[0047] In the hot stamping aluminum-plated steel sheet of the present embodiment, the temperature rise rate during hot stamping heating can be increased by applying a predetermined surface treatment film described later to the entire surface of at least one surface of the coating layer. Specifically, the productivity of the hot stamping component can be further improved by heating the HS aluminum-plated steel sheet having the predetermined surface treatment film and hot stamping the heated aluminum-plated steel sheet for hot stamping.

[0048] <Surface treatment film>

[0049] Figure 1 A schematic cross-sectional view showing a surface portion of one of the surfaces of the aluminum-plated steel sheet for hot stamping according to the present embodiment.

[0050] like Figure 1As shown in , the aluminum-plated steel sheet 10 for hot stamping of the present embodiment has, for example: a base steel sheet 11; an aluminum coating (Al coating) 12 provided on at least one surface of the base steel sheet 11; and a surface treatment film 13 provided on the aluminum coating 12. In the aluminum-plated steel sheet 10 for hot stamping of the present embodiment, the surface on the side of the surface treatment film 13 (i.e., the surface of the surface treatment film 13) has a high emissivity. Therefore, the heating rate during hot stamping heating is high, and as a result, the productivity of hot stamping components can be further improved. It should be noted that Figure 1 The dimensions of the surface treatment film 13 and the aluminum plating layer 12 are not necessarily shown in the preferred embodiment and are not limited to Figure 1 Size, etc.

[0051] The surface treatment film 13 of the present embodiment contains: a compound A containing carbon; and a compound B which is an oxide or a fluoride of a metal element M and has a rutile structure.

[0052] The surface treatment film 13 of the present embodiment may further contain an adhesive component as needed. In addition, the surface treatment film 13 of the present embodiment may also contain silicon dioxide. Furthermore, in the present embodiment, by adjusting the content of compound A and compound B in the surface treatment film 13, the concentration distribution of the metal element M, the coating and drying method of the surface treatment film 13, and the film thickness, etc., it is possible to achieve an increase in the heating rate (heating efficiency) during hot stamping heating.

[0053] In addition, in the surface treatment film 13 of the present embodiment, compound B has a prescribed concentration distribution. Specifically, the concentration of the metal element M constituting compound B relative to the film has a concentration distribution (concentration inclination) in which the coating side is greater than the surface side of the film in the film thickness direction. By having the metal element M in such a prescribed concentration distribution, the heating efficiency generated by the surface treatment film 13 can be further improved. When the hot stamping steel plate of the present embodiment is heated for hot stamping, the radiant heat from the heated atmosphere can be efficiently absorbed. In addition, heat can also be efficiently absorbed by heat conduction generated by contact with the heated atmosphere gas. As a result, the entire surface treatment film can be quickly heated.

[0054] Hereinafter, constituent elements of the surface treatment film 13 will be described in detail.

[0055] [Compound A]

[0056] The carbon concentration of compound A contained in the surface treatment film 13 is 80% by mass or more. When the carbon concentration of compound A is less than 80% by mass, when the HS is heated with an aluminum-plated steel sheet in the hot stamping process, compound A will be decomposed and oxidized even at a relatively low temperature, so compound A may disappear from the film. If compound A disappears from the film, the effect of improving the temperature rise characteristics cannot be maintained to a high temperature. Therefore, the carbon concentration of compound A is set to 80% by mass or more. Preferably, the carbon concentration of compound A is 82% by mass or more, preferably 85% by mass or more. The carbon concentration of compound A may also be 100% by mass.

[0057] Examples of the compound A include carbon black (CB), graphite, and soot.

[0058] The carbon concentration of the compound A can be measured by cross-sectional analysis of the surface-treated film using a transmission electron microscope (TEM), energy dispersive X-ray spectroscopy (EDS), and electron beam diffraction.

[0059] Specifically, the spectrum of characteristic X-rays during electron beam irradiation is measured, and the detection intensity of each energy is calculated. The elements constituting the compound to be measured can be determined from the energy value. Then, a standard line pre-made from the relationship between a substance with known element concentration and its detection intensity data is used to calculate the concentration of each element in the compound from the detection intensity of each element constituting the compound to be measured. When the measurement is carried out 10 times in the same compound, if the maximum value of the concentration of each element of all elements falls within the range of 1.0 to 1.3 times the minimum value, it is considered to be the same compound. That is, when 10 measurements are made in one compound observed by TEM-EDS, if the maximum value of the concentration of all elements constituting the compound falls within the range of 1.0 to 1.3 times the minimum value, it is considered to be the same compound.

[0060] The TEM observation sample was prepared by a focused ion beam (FIB) processing and observation apparatus (eg, "NB5000" manufactured by Hitachi High-Tech Co., Ltd.) using a FIB sampling method. The acceleration voltage during processing was set to 40 kV.

[0061] The carbon concentration of compound A is defined as follows. In the cross-sectional analysis of the surface treatment film, within the range surrounded by the film thickness and the length 5 μm in the direction orthogonal to the film thickness, the intermediate value between the maximum and minimum carbon concentrations measured at 10 locations in the same compound is taken as the carbon concentration of compound A. In the case where there are multiple compounds A within the above range, the intermediate value is calculated in each compound A, and the average value of the intermediate value obtained is taken as the carbon concentration of compound A. By such a method, the concentration of elements such as carbon constituting compound A can be analyzed. It should be noted that compound A with carbon as the main component and compound B as an oxide or fluoride of the metal element M can be distinguished by the difference in carbon concentration.

[0062] Furthermore, in the present embodiment, when the average thickness of the surface treatment film is set to H (μm), the content of compound A having a carbon concentration of 80% by mass or more is preferably 10 to 90% or 20 to 90%, and more preferably 30 to 80% at a position 0.90H away from the surface of the surface treatment film (hereinafter also referred to as "interface side position P". The interface side position P can be said to be a position 0.10H away from the interface between the surface treatment film and the Al plating layer).

[0063] Compound A having a carbon concentration of 80% by mass or more has a large effect of absorbing radiant heat. In addition, such compound A is not easy to disappear from the surface treatment film due to decomposition and volatilization caused by heating due to its high carbon concentration. Therefore, even when the temperature of the outermost surface of the aluminum-plated steel sheet for HS is increased by heating of hot stamping, the absorption of radiant heat can be increased until the high temperature region. In order to obtain such an effect, it is effective to increase the content of compound A. In the present embodiment, by preferably setting the content of compound A at the interface side position P to 10% or more or 20% or more, more preferably to 30% or more, the heating rate during hot stamping heating can be further increased. On the other hand, compound A in the surface treatment film itself does not have the effect of improving the adhesion of the film. Therefore, in the surface treatment film, the content of compound A at the interface side position P, especially the Al coating side, is preferably suppressed to a prescribed amount or less. Specifically, by preferably setting the content of compound A at the interface side position P to 90% or less, more preferably to 80% or less, the adhesion of the surface treatment film to the Al coating is improved. It is believed that the mechanism for improving the adhesion of the film by preferably setting the content of compound A at the interface side position P to less than 90%, more preferably less than 80%, can ensure the chemical and physical bonding of the highly polar rutile compound and binder resin contained in the surface treated film with the aluminum plating layer, resulting in the effect of improving the adhesion of the film.

[0064] The content of compound A at the interface side position P is determined by the following method.

[0065] First, by TEM observation, compound A having a carbon concentration of 80% or more is detected by EDS at the interface side position P. The "0.90H position" is, for example, a position at a depth (thickness) of 4.5 μm from the surface of the surface treatment film when the average thickness H of the surface treatment film is 5 μm (i.e., a position at a depth (thickness) of 0.5 μm from the interface between the surface treatment film and the Al plating layer toward the film side).

[0066] Next, in the TEM image of the sample described later, when 10 points are observed at intervals of 30 nm in a direction perpendicular to the thickness direction of the surface treatment film layer (a direction parallel to the interface between the aluminum plating layer and the surface treatment film, and perpendicular to the thickness direction of the sample), when the presence of the compound A is observed at 3 points, the content of the compound A at the interface side position P is defined as 30%. Similarly, when the presence of the compound A is observed at 4 points, the content of the compound A is defined as 40%, and the same is set hereinafter. Therefore, when the compound A having a carbon concentration of 80% or more is observed at 3 to 8 points, it means that the content of the compound A is 30 to 80%.

[0067] The TEM observation sample used for calculating the content of compound A was prepared by a focused ion beam (FIB) processing observation device (e.g., "NB5000" manufactured by Hitachi High-Tech Co., Ltd.) using the FIB sampling method. The acceleration voltage during processing was set to 40 kV. The thickness of the sample was set to 100 nm ± 10 nm.

[0068] It should be noted that the content of compound A is a ratio (%) calculated from the ratio of the number of points where compound A is observed (existed) in 10 points in a specific direction (a direction parallel to the surface of the surface treatment film and a direction perpendicular to the thickness direction of the sample) in the TEM image of a sample with a thickness of 100±10nm (=the number of points where compound A exists / 10). Therefore, the unit of the content is not volume % or area %, but % with a dimension of 1.

[0069] [Compound B]

[0070] Compound B is an oxide or fluoride of a metal element M and has a rutile structure. As the metal element M, Ti, V, Mn, Ru, Cs, Ir, Ge, Cu, Ag, Ni, etc. can be listed. As required, any one or more of the above elements can be used as the metal element M. In addition, as such a compound B, TiO2, VO2, β-MnO2, RuO2, CsO2, IrO2, GeO2, CuO2, AgO2, NiF2, etc. can be listed. As required, any one or more of the above compounds can be used as compound B.

[0071] By including the compound B having a rutile compound structure in the film, the heating rate during hot stamping can be increased. The reason for this is not clear, but is presumed as follows.

[0072] The rutile structure is a structure in which anions are skewed and hexagonally packed, and cations are arranged in the 6-coordinate space (6-coordinate gap). In addition, it is estimated that when the film contains compound B having a rutile compound structure, the radiation generated by electromagnetic waves in the infrared or near-infrared region, which is the main heating factor, becomes an active inter-ion distance during hot stamping heating, thereby increasing the heating rate during hot stamping.

[0073] It should be noted that the crystal structure of compound B and the type of compound (whether it is an oxide or a fluoride) can be determined by using a cross-sectional analysis of a surface-treated film of TEM, EDS and electron beam diffraction. Specifically, the electron beam diffraction image during electron beam irradiation is compared with a pre-existing database. If the compound is classified as a rutile structure, it can be determined that the compound has a rutile structure. In addition, by EDS, the compound can be determined by the ratio of element concentration, and then when the ratio of oxygen or fluorine is more than 10% by mass, it can be determined that the compound is an oxide or a fluoride.

[0074] In addition, in the present embodiment, the concentration of the metal element M in the compound B satisfies the following formula (1) and the following formula (2).

[0075] 1≤C bM ≤40 Formula (1)

[0076] 1.5≤C bM / C tM ≤10.0 Formula (2)

[0077] When the average thickness of the surface treatment film is set to H (μm), C in the above formula (2) is tMis the concentration (mass %) of the metal element M at a position 0.05H from the surface of the surface treatment film 13. C in the above formula (1) and the above formula (2) bM It is the concentration (mass %) of the metal element M at a position 0.95H from the surface of the surface treatment film 13 .

[0078] like Figure 1 As shown in FIG. 1 , when the thickness of the surface treatment film 13 is set to H (μm), the concentration C of the metal element M at a distance of 0.95H from the surface of the surface treatment film 13 is bM The mass % is 1% to 40%.

[0079] In C bM If the C content is less than 1%, it becomes difficult to improve the temperature rise characteristics during heating in hot stamping, especially in the high temperature range. bM Set to 1% or more. bM It is preferably 5% or more, and more preferably 8% or more. bM When the temperature is set to 8% or more, the heating rate during hot stamping can be further increased. bM When the concentration C in the surface treatment film 13 near the Al plating layer 12 is higher than 40%, the heating rate during hot stamping is saturated, and the adhesion between the surface treatment film 13 and the Al plating layer 12 is reduced. This is because the compound B is relatively hard, so if the concentration C in the surface treatment film 13 near the Al plating layer 12 is bM As the C increases, the followability of the surface treatment film 13 to the fine irregularities on the surface of the Al plating layer 12 decreases. bM It is set to 40% or less. This can increase the heating rate during hot stamping and improve the film adhesion. bM It is preferably 35% or less, more preferably 30% or less, and still more preferably 20% or less. bM By setting the content to 20% or less, the adhesion between the surface treatment film 13 and the aluminum plating layer 12 can be further improved.

[0080] In addition, as shown in the above formula (2), C bM / C tM It is 1.5~10.0.

[0081] The concentration of the metal element M near the interface between the Al plating layer 12 and the surface treatment film 13 is high. bM / C tM When the ratio is 1.5 or more, the metallic luster of the surface of the Al plating layer 12 can be concealed, and the reflection of radiant heat can be suppressed. bM / C tMPreferably it is 2.0 or more, more preferably 3.0 or more. On the other hand, if C bM / C tM If C is greater than 10.0, the surface side of the surface treatment film 13 will not absorb enough heat, and as a result, the temperature rise rate during hot stamping cannot be increased. bM / C tM It is set to 10.0 or less. This makes it possible to control the reflection of radiant heat on the surface of the Al plating layer 12 and the heat absorption state on the surface side of the surface treatment film 13 to an appropriate state and increase the temperature rise rate. bM / C tM It is preferably 8.0 or less, and more preferably 6.0 or less.

[0082] The concentration (mass %) of the metal element M at a distance of 0.05H from the surface of the surface treatment film 13 is C tM and the concentration C of the metal element M at 0.95H from the surface of the surface treatment film 13 bM like Figure 1 As shown in , when the thickness of the surface treatment film 13 is set to H (μm), it can be measured by fluorescent X-ray analysis and glow discharge emission spectroscopy (GDS).

[0083] Below, for C bM and C tM The method of finding is described in detail.

[0084] First, the average concentration (mass %) of the metal element M is determined as follows.

[0085] Using an aluminum-plated steel sheet to which a surface treatment film containing compound A and compound B (oxide or fluoride of metal element M) was applied, the detection intensity (kcps, counts per second 10) of metal element M was determined by fluorescent X-ray analysis. 3 (10 3 It should be noted that the adhesion amount (g / m2) of the metal element M in the surface treatment film was prepared in advance by fluorescent X-ray according to JIS K 0119 (2008). 2 ) and the standard line of detection intensity (kcps) of metal element M.

[0086] Using this standard line, the adhesion amount P (g / m2) of the metal element M in the surface treatment film was determined from the detection intensity (kcps) of the metal element M obtained by fluorescent X-ray analysis. 2). It should be noted that when the detection intensity of the metal element M in the surface treatment film is obtained by the fluorescent X-ray analysis method, the concentration of the metal element M in the base steel material has no effect, that is, it can be ignored. That is, since the fluorescent X-rays are greatly attenuated by the metal elements of the aluminum coating and the surface treatment film, the elements in the base steel material deeper than the aluminum coating and the surface treatment film can be regarded as having no effect on the detection intensity of the metal element M in the surface treatment film.

[0087] Next, the metal element M is measured along the depth direction of the surface treatment film 13 by GDS, and the thickness of the surface treatment film 13 is determined by defining the interface between the surface treatment film and the Al plating layer at a position where the intensity of the metal element M becomes less than 1 / 2 at a depth (thickness) position closer to the base steel plate than the maximum value of the intensity. The thickness is measured at 5 locations, and the average value of the obtained thickness is taken as the thickness H (μm) of the surface treatment film 13. Then, the value "P×100 / H" obtained by dividing the amount P of metal element M attached by H and multiplying by 100 is regarded as the average concentration (mass %) of the metal element M in the surface treatment film in the entire depth direction.

[0088] On the other hand, the concentration of the metal element M at any position in the depth direction of the surface treatment film can be obtained by using the relationship between the average value of the intensity of the metal element M from the surface of the surface treatment film to the interface with the Al plating layer measured by GDS and the above-mentioned average concentration P×100 / H to be in a 1:1 ratio. That is, the average concentration (mass %) of the metal element M in the entire film thickness, i.e., P×100 / H, and the average value α of the intensity of the metal element M from the surface to the interface with the Al plating layer are respectively obtained.

[0089] On the other hand, if the intensity (kcps) of the metal element M at an arbitrary position X in the depth direction is set to β, the concentration C of the metal element M at the position X is XM (mass %) can be calculated by the following formula (3) using the proportional relationship.

[0090] C XM =P / H×100×(β / α) (3)

[0091] The average concentration (mass %) of the metal element M at 0.05H obtained using the formula (3) is defined as C tM , the concentration (mass %) of the metal element M at a position 0.95H from the surface is set to C bM .

[0092] In the present embodiment, compound B is preferably rutile TiO 2. When compound B is rutile TiO 2, the heating rate during hot stamping can be further increased. The reason is not clear, but it is estimated as follows.

[0093] Compared with compounds such as Al2O3 that are usually generated on the surface of the aluminum plating layer during the heating process of hot stamping, rutile TiO2 can maintain a high emissivity even in the high temperature range from 300°C to 900°C. Therefore, it is speculated that the heat input generated by radiation can be increased. In addition, when the temperature is further increased to the high temperature range, a composite oxide of rutile TiO2 and Al2O3 may be formed. It is speculated that the emissivity of the composite oxide of rutile TiO2 and Al2O3 is also higher than that of other oxides, which is also a factor that can further increase the heating rate during hot stamping.

[0094] Compound B is an oxide or fluoride of the metal element M, but compound B may also be composed of two or more compounds. For example, in the surface treatment film, TiO2 and VO2 may also be included as compound B. It should be noted that when two or more compounds are included as compound B in the surface treatment film, the compound with the largest content may satisfy the desired concentration and distribution as described in (1) and (2) above.

[0095] It should be noted that, when preparing a treatment solution containing compound A and a compound B having a rutile structure which is an oxide or fluoride of a metal element M, and a treatment solution containing organic and inorganic substances such as a resin which is an adhesive component, and forming a laminated film by coating these treatment solutions on the aluminum plating layer, compound B will not exist in a prescribed concentration distribution as described above. In addition, if you want to use a plurality of treatment solutions to form a multilayer surface treatment film like this, you must form a second layer of film after forming the first layer of film, so the manufacturing equipment is large-scale, and the manufacturing cost is also increased. Therefore, the surface treatment film 13 of the present embodiment is not a multilayer structure, but needs to be a single-layer structure.

[0096] The aluminum-plated steel sheet 10 for hot stamping of the present embodiment has the surface treatment film 13 having the above-mentioned characteristics, and can increase the heating rate during hot stamping. Therefore, by using the aluminum-plated steel sheet 10 for hot stamping of the present embodiment as a raw material, the productivity of hot stamping materials can be improved.

[0097] The reason why the surface treatment film 13 of this embodiment can increase the temperature rise rate of the steel sheet during hot stamping is not clear, but the presence of a large number of bonds active for infrared rays with a wavelength of 1 to 10 μm, which are particularly effective in absorbing radiant heat, is considered to be a possible reason.

[0098] In the surface treatment film 13 of the present embodiment, in addition to the above-mentioned compound A and compound B, resins and additives as various adhesive components may be contained. By containing resin, the adhesion between the surface treatment film 13 and the Al plating layer 12 can be improved. As additives contained in the surface treatment film 13, for example, leveling agents, defoaming agents, colorants, viscosity modifiers, ultraviolet absorbers, etc. can be listed. The coating liquid for forming the surface treatment film 13 is preferably obtained by dispersing or dissolving the above-mentioned components in water or a solvent.

[0099] In this embodiment, specific methods for imparting the surface treatment film 13 include coating and lamination, but are not limited to these methods. The surface treatment film 13 may be imparted to only one surface of the aluminum-plated steel plate or to both surfaces of the aluminum-plated steel plate.

[0100] When the surface treatment film 13 is to be applied to the entire surface of the aluminum plating layer 12 by coating, first, for example, a treatment liquid containing a compound A having a carbon concentration of 80% by weight or more and a compound B having a rutile structure which is an oxide or fluoride of a metal element M is prepared. Then, the treatment liquid is applied to the entire surface of the aluminum plating layer 12 by a roll coater, a curtain coater, an inkjet, etc., and the volatile components in the treatment liquid are dried to provide the surface treatment film 13. In particular, coating by inkjet is preferred because the film thickness can be continuously changed.

[0101] Here, in the past (e.g., Patent Document 2, etc.), when organic matter such as carbon pigment is included in the surface treatment film, if the plated steel sheet is heated to a high temperature region (e.g., above 750°C), these organic matter disappears, and there is a problem of deterioration of the heating characteristics (heating rate). However, the inventors of the present invention have found that in the case of the surface treatment film 13 of the present embodiment, even if the organic matter disappears, it can be efficiently heated to the high temperature region. The mechanism by which heating to the high temperature region can be achieved even if the organic matter disappears is not clear, but it is presumed that the compound B (oxide or fluoride of the metal element M) contained in the film increases the heat input generated by radiation at high temperatures.

[0102] [Binder component (resin)]

[0103] The content of the binder component (resin) that can be contained in the surface treatment film 13 of the present embodiment is preferably 40% by volume or more relative to the total volume of the surface treatment film 13. As the binder component, various known resins can be used.

[0104] The resin as the binder component is not particularly limited. For example, polyurethane resin, polyester resin, acrylic resin, epoxy resin, fluororesin, polyamide resin, polyolefin resin, polymer compounds obtained by hydrolyzing / polycondensing silane coupling agents can be listed. As resin, resins obtained by crosslinking these resins through butylated melamine resin, methylated melamine resin, butyl methyl mixed melamine resin, urea resin, isocyanate resin or the crosslinking agent components of these mixed systems can also be listed. In addition, electron beam curing resins, ultraviolet curing resins, etc. can also be listed. Among them, the resin as the binder component is preferably any one or more of polyester resin, epoxy resin, acrylic resin and polyurethane resin. The resins as these binder components can be used alone, or two or more can be mixed and used.

[0105] When a polyurethane resin is used as the binder component, for example, the polyurethane resin is preferably a polyether-based polyurethane resin. This is because the use of a polyether-based polyurethane resin can prevent the occurrence of hydrolysis caused by acid or alkali compared to a polyester-based polyurethane resin, and because the formation of a hard and brittle film can be suppressed compared to a polycarbonate-based polyurethane resin, so that the adhesion during processing and the corrosion resistance of the processed portion can be ensured.

[0106] Whether the polyurethane resin is contained can be determined based on whether a 3330 cm-1 infrared absorption spectrum is observed. -1 (NH telescopic), 1730cm -1 (C=O stretching), 1530cm -1 (CN), 1250cm -1 The content of the polyurethane resin can also be determined by using a sample with a known content in advance, creating a standard line showing the relationship between the content and the intensity of the characteristic absorption, and then determining the content from the obtained characteristic absorption intensity.

[0107] In addition, the presence and content of resins other than the above-mentioned polyurethane resins can also be determined in the same manner as the above-mentioned polyurethane resins by focusing on the characteristic absorption derived from the functional groups unique to each resin. As components in the treatment liquid for dispersing or dissolving the resin, water or a solvent can be used.

[0108] [additive]

[0109] The surface treatment film 13 of the present embodiment may contain various additives such as a leveling agent, a water-soluble solvent, a metal stabilizer, an etching inhibitor, etc. as additives in preparing a treatment liquid before film formation within a range that does not impair the effects of the present invention.

[0110] As the leveling agent, examples of nonionic or cationic surfactants include polyethylene oxide or polypropylene oxide adducts and acetylene glycol compounds.

[0111] Examples of the water-soluble solvent include alcohols such as ethanol, isopropanol, tert-butyl alcohol and propylene glycol, cellosolves such as ethylene glycol monobutyl ether and ethylene glycol monoethyl ether, esters such as ethyl acetate and butyl acetate, and ketones such as acetone, methyl ethyl ketone and methyl isobutyl ketone.

[0112] Examples of the metal stabilizer include chelate compounds such as EDTA (ethylenediaminetetraacetic acid) and DTPA (diethylenetriaminepentaacetic acid).

[0113] Examples of the etching inhibitor include amine compounds such as ethylenediamine, triethylenepentamine, guanidine, and pyrimidine.

[0114] In addition, the content of the above-mentioned binder component and additive can also be measured in the same manner as in the case of the above-mentioned compounds A and B.

[0115] [Silicon dioxide]

[0116] The surface treatment film 13 of the present embodiment may contain silicon dioxide. When silicon dioxide is contained, the content of silicon dioxide is preferably 0.01 to 0.3 g / m 2 . By containing 0.01g / m 2 The above silicon dioxide can prevent the occurrence of defects in the film due to contact with other steel plates, equipment and machinery. 2 In the case of silicon dioxide, the temperature rise effect cannot be expected, and on the other hand, it becomes costly, so it is not preferred in terms of economic efficiency. In addition, since silicon dioxide is a substance with low electrical conductivity, when containing more than 0.3 g / m 2 In the case of silicon dioxide, it is not preferred in terms of weldability after hot stamping. In the case of silicon dioxide, the content of silicon dioxide in the surface treatment film 13 is as small as possible. The content of silicon dioxide in the surface treatment film is more preferably 0.10 g / m 2 Below, more preferably 0.05 g / m 2 the following.

[0117] [Thickness of surface treatment film]

[0118] The average film thickness H of the surface treatment film 13 containing the above-mentioned components is preferably set to, for example, 0.5 to 15.0 μm.

[0119] When the average film thickness of the surface treatment film 13 is less than 0.5 μm, the absorption of radiant heat is insufficient, and therefore the heating rate during hot stamping cannot be sufficiently increased. On the other hand, when the average film thickness of the surface treatment film 13 exceeds 15.0 μm, the heat capacity of the surface treatment film 13 itself becomes large, and becomes an obstacle when heat moves to the aluminum plating layer 12. As a result, the heating rate cannot be fully increased, and it is not preferred in terms of economy because of the increased cost. By setting the average film thickness of the surface treatment film 13 to a range of 0.5 to 15.0 μm, the heating rate can be increased. The average film thickness of the surface treatment film 13 is more preferably 1.0 to 7.0 μm.

[0120] <Base treatment film>

[0121] Between the surface treatment film 13 and the aluminum plating layer 12, such as Figure 2 As shown in , in order to improve the adhesion of the surface treatment film 13, a base treatment film (chemical conversion treatment layer) 14 may also be provided. Figure 2 The dimensions of the surface treatment film 13, the aluminum plating layer 12, and the base treatment film 14 do not necessarily represent a preferred embodiment and are not limited to Figure 2 Size, etc.

[0122] The base treatment film 14 may also include any one or more selected from resin, silane coupling agent, zirconium compound, silicon dioxide, phosphoric acid and its salt, fluoride and vanadium compound. If these substances are included, the film-forming property after the chemical conversion treatment agent is applied, the barrier property (compactness) of the film to corrosion factors such as moisture or corrosive ions, and the film adhesion to the plated surface are further improved, which helps to improve the level of corrosion resistance of the film. In particular, if the chemical conversion treatment layer includes any one or more of a silane coupling agent and a zirconium compound, a cross-linked structure is formed in the film, and the bonding with the plated surface is also strengthened, so that the adhesion and barrier property of the film can be improved.

[0123] Furthermore, if the base treatment film 14 contains one or more of silicon dioxide, phosphoric acid and its salts, fluorides, and vanadium compounds, it can improve corrosion resistance by forming a precipitated film or a passive film on the plated surface or the base steel sheet surface as an inhibitor.

[0124] [Attachment amount of base treatment film 14]

[0125] The amount of the base treatment film 14 deposited on one side of the plated layer is preferably 10 to 1000 mg / m2 in terms of solid content. 2 The adhesion amount of the base treatment film 14 is less than 10 mg / m 2If the adhesion amount of the base treatment film 14 exceeds 1000 mg / m 2 , then there is a possibility that the processing adhesion will decrease.

[0126] The amount of the base treatment film 14 deposited on one side of the plated layer is more preferably 20 to 800 mg / m 2 , more preferably 50 to 600 mg / m 2 .

[0127] <Aluminum coating>

[0128] The aluminum-plated steel sheet 10 for hot stamping of the present embodiment preferably has an aluminum coating 12 on the base steel sheet 11 on at least one surface of the base steel sheet 11. By having the aluminum coating 12, the corrosion resistance after painting after hot stamping can be further improved. In addition, by having the aluminum coating 12 between the base steel sheet 11 and the surface treatment film 13, it is possible to prevent the formation of iron oxide scale due to heating during hot stamping. Iron oxide scale becomes a burden on manufacturing because it contaminates the heating furnace and adheres to the rollers used for transportation. Therefore, when iron oxide scale is generated, in order to remove the iron oxide scale, processes such as shot peening become necessary, which is not economically preferred.

[0129] The type of the aluminum plating layer is not particularly limited. The composition constituting the aluminum plating layer includes aluminum plating, Al-Si plating, Al-Si-Mg, Al-Si-Ca plating, and the like.

[0130] For example, the chemical composition (average chemical composition) of the aluminum plating layer may be as follows: in mass %, it contains Al: 80.0-95.0%, Si: 2.0-15.0%, Fe: 1-15.0%, Cr: 0% or more and less than 1.0%, Mo: 0% or more and less than 1.0%, Zn: 0% or more and less than 1.0%, V: 0% or more and less than 1.0%, Ti: 0% or more and less than 1.0%, Sn: 0% or more and less than 1.0%, Ni: 0% or more and less than 1.0%, Cu: 0% or more and less than 1.0%, W: 0% or more and less than 1.0%, Bi: 0% or more and less than 1.0%, Mg: 0% or more and less than 1.0%, Ca: 0% or more and less than 1.0%, and the remainder is impurities.

[0131] If the Al content in the aluminum plating layer is less than 80.0%, the corrosion resistance after hot stamping (corrosion resistance of the hot stamped formed body) deteriorates. Therefore, the Al content is preferably 85.0% or more. The Al content is more preferably 88.0% or more. On the other hand, if the Al content in the aluminum plating layer exceeds 95.0%, the plating adhesion may deteriorate. Therefore, the Al content is preferably set to 95.0% or less. The Al content is more preferably 92.0% or less.

[0132] If the Si content in the aluminum plating layer is less than 2.0%, the plating adhesion may be deteriorated. Therefore, the Si content is preferably set to 2.0% or more. The Si content is more preferably 3.0% or more, and further preferably 4.0% or more. On the other hand, if the Si content in the aluminum plating layer exceeds 15.0%, the plating adhesion may be deteriorated. Therefore, the Si content is preferably set to 15.0% or less. The Si content is more preferably 13.0% or less.

[0133] The Fe content is preferably 1.0% or more and 15.0% or less.

[0134] The chemical composition of the aluminum plating layer can be measured by the fluorescent X-ray method in accordance with JIS G K0119: 2008. That is, using a sample with a known content of the target element, the relationship between the X-ray intensity and the content is determined in advance. The content of each element of the unknown sample, i.e., the chemical composition, can be determined from the standard curve made based on this relationship.

[0135] [Aluminum coating adhesion]

[0136] The aluminum plating layer 12 is applied to one or both sides of the base steel plate 11. The coating weight is preferably 5 g / m2 per side. 2 ~140g / m 2 .

[0137] The adhesion amount on each side is less than 5g / m 2 In the case of hot stamping, iron scale is generated on the surface of the base steel plate during the heating process, and a process of removing the scale is required. On the other hand, when the adhesion amount per single side exceeds 140g / m 2 In the case of 50 g / m2, it takes time to allow the alloying reaction of Al and Fe in the hot stamping heating process required to improve the corrosion resistance after coating to proceed, which is not preferred from the perspective of productivity. Therefore, the adhesion amount of the aluminum plating layer 12 is preferably 5 g / m2 per single side. 2 ~140g / m 2 .

[0138] <Base Steel Plate>

[0139] Next, the base steel plate 11 of the hot stamping aluminum-plated steel plate 10 of the present embodiment is described. The base steel plate 11 is not particularly limited as long as it can be suitably used in the hot stamping method. The chemical composition of the base steel plate 11 of the hot stamping aluminum-plated steel plate 10 applicable to the present embodiment can also be calculated as follows in mass %, for example:

[0140] C: 0.03~0.60%,

[0141] Si: 0.01-0.60%,

[0142] Mn: 0.50~3.00%,

[0143] P: 0.050% or less,

[0144] S: 0.020% or less,

[0145] Al: 0.100% or less,

[0146] Ti: 0.01-0.10%,

[0147] B: 0.0001~0.0100%,

[0148] N: 0.010% or less,

[0149] Cr: 0~1.00%,

[0150] Ni: 0-2.00%,

[0151] Cu: 0~1.000%,

[0152] Mo: 0-1.00%,

[0153] V: 0~1.00%,

[0154] Nb: 0-1.00%,

[0155] Sn: 0~1.00%,

[0156] W: 0~1.00%,

[0157] Ca: 0~0.010%

[0158] REM: 0~0.30%,

[0159] The remainder: Fe and impurities.

[0160] In addition, as a form of the base material steel plate 11, for example, a steel plate such as a hot-rolled steel plate and a cold-rolled steel plate can be exemplified.

[0161] The preferred ranges of the elements of the base steel plate 11 of the hot stamping aluminum-plated steel sheet 10 and the reasons thereof are described in detail below. In the following description of the chemical composition of the base steel plate 11, "%" means "mass %" unless otherwise specified.

[0162] [C: 0.03~0.60%]

[0163] C is contained in order to ensure the target mechanical strength. When the C content is 0.03% or more, sufficient improvement in mechanical strength can be obtained, and the effect of containing C can be fully obtained. Therefore, the C content is preferably 0.03% or more. The C content is more preferably 0.20% or more. On the other hand, when the C content is 0.60% or less, the strength hardening of the steel sheet can be improved, and the reduction in elongation and drawing can be suppressed. Therefore, the C content is preferably 0.60% or less. The C content is more preferably 0.40% or less.

[0164] [Si: 0.01 to 0.60%]

[0165] Si is one of the strength-enhancing elements that improves mechanical strength, and is contained in order to ensure the target mechanical strength, similar to C. When the Si content is 0.01% or more, the strength-enhancing effect can be fully exerted, and a sufficient improvement in mechanical strength can be obtained. Therefore, the Si content is preferably 0.01% or more. The Si content is more preferably 0.10% or more. On the other hand, Si is also an easily oxidizable element, so when the Si content is 0.60% or less, the decrease in wettability during hot-dip Al plating caused by the influence of Si oxides formed on the surface of the steel plate can be suppressed, and the occurrence of unplated can be suppressed. Therefore, the Si content is preferably 0.60% or less. The Si content is more preferably 0.40% or less.

[0166] [Mn: 0.50~3.00%]

[0167] Mn is one of the strengthening elements that strengthen steel and is also one of the elements that improve hardenability. Furthermore, Mn is an element that is also effective in preventing hot brittleness caused by S, which is one of the impurities. These effects can be fully obtained by having a Mn content of more than 0.50%. Therefore, in order to reliably show the above effects, the Mn content is preferably more than 0.50%. The Mn content is more preferably more than 0.80%. On the other hand, since Mn is an austenite-forming element, the Mn content is less than 3.00%, so that the retained austenite phase does not become too much, and the reduction in strength can be suppressed. Therefore, the Mn content is preferably less than 3.00%. The Mn content is more preferably less than 1.50%.

[0168] [P: 0.050% or less]

[0169] P is an impurity contained in steel. By setting the P content to 0.050% or less, it is possible to suppress the P contained in the steel plate from segregating at the crystal grain boundaries of the steel plate and reducing the toughness of the base material of the formed body after hot stamping, and to suppress the reduction in the delayed fracture resistance of the steel plate. Therefore, the P content is preferably 0.050% or less, and the P content is preferably reduced as much as possible. As needed, the P content can also be set to 0.045% or less or 0.040%. The lower limit of the P content is 0%, but the lower limit can also be set to 0.001% or 0.005%.

[0170] [S: 0.020% or less]

[0171] S is an impurity contained in steel. When the S content is 0.020% or less, it is possible to suppress the S contained in the steel plate from forming sulfides and reducing the toughness of the steel plate, and it is possible to suppress the reduction in delayed fracture resistance of the steel plate. Therefore, the S content is preferably 0.020% or less, and the S content is preferably reduced as much as possible. If necessary, the S content may be set to 0.015% or less or 0.010% or less. The lower limit of the S content is 0%, but the lower limit may also be set to 0.001% or 0.002%.

[0172] [Al: 0.100% or less]

[0173] Al is generally used for the purpose of deoxidation of steel. On the other hand, by making the Al content 0.100% or less, the rise of the Ac3 point of the steel plate can be suppressed, so the heating temperature required to ensure the hardenability of the steel can be reduced during hot stamping, which is preferred in hot stamping manufacturing. Therefore, the Al content of the steel plate is preferably 0.100% or less, more preferably 0.050% or less, and further preferably 0.030% or less. The lower limit of the Al content is 0%, but the lower limit can also be set to 0.001%, 0.003% or 0.007%.

[0174] [Ti: 0.01~0.10%]

[0175] Ti is one of the strength strengthening elements. When the Ti content is 0.01% or more, the strength improvement effect and the oxidation resistance improvement effect can be fully obtained. Therefore, in order to reliably show the above effects, the Ti content is preferably 0.01% or more. The Ti content is more preferably 0.03% or more. On the other hand, when the Ti content is 0.10% or less, for example, the formation of carbides and nitrides can be suppressed, the softening of steel can be suppressed, and the target mechanical strength can be fully obtained. Therefore, the Ti content is preferably 0.10% or less. The Ti content is more preferably 0.08% or less.

[0176] [B: 0.0001~0.0100%]

[0177] B has the effect of improving strength by acting during quenching. Such a strength improvement effect can be fully obtained by a B content of 0.0001% or less. Therefore, the B content is preferably 0.0001% or more. The B content is more preferably 0.0010% or more. On the other hand, by a B content of 0.0100% or less, the formation of inclusions is reduced and the embrittlement of the steel plate is suppressed, and the reduction in fatigue strength can be suppressed. Therefore, the B content is preferably 0.0100% or less. The B content is more preferably 0.0040% or less.

[0178] [N: 0.010% or less]

[0179] N is an impurity contained in steel. When the N content is 0.010% or less, the formation of nitrides caused by N contained in the steel plate can be suppressed, and the toughness reduction of the steel plate can be suppressed. Furthermore, when B is contained in the steel plate, the N contained in the steel plate can be suppressed from combining with B to reduce the amount of solid solution B, and the reduction of the hardenability improvement effect of B can be suppressed. Therefore, the N content is preferably 0.010% or less, and the N content is more preferably reduced as much as possible.

[0180] In addition, the base steel sheet of the hot stamping steel sheet of the present embodiment may further contain one or more elements selected from Cr, Mo, Ni, Cu, V, Nb, Sn, W, Ca and REM as optional elements. The lower limit of the content of these elements is 0%.

[0181] [Cr: 0~1.00%]

[0182] Cr is an element that improves the hardenability of the steel sheet. In order to fully obtain the above effect, it is preferred that the Cr content be set to 0.01% or more. On the other hand, by setting the Cr content to 1.00% or less, the effect can be fully obtained and the cost increase can be suppressed. Therefore, the Cr content in the case of containing Cr is preferably set to 1.00% or less. As required, the Cr content can also be set to 0.70% or less or 0.50% or less.

[0183] [Ni: 0~2.00%]

[0184] Ni is an element that can improve the hardenability of steel and stably ensure the strength of the steel plate component after quenching. In order to fully demonstrate the above effect, it is preferred that the Ni content is set to more than 0.10%. On the other hand, by having a Ni content of less than 2.00%, the above effect can be fully obtained, and the economy is improved. Therefore, the Ni content in the case of containing Ni is preferably set to less than 2.00%. As required, the Ni content can also be set to less than 1.20%, less than 0.80% or less than 0.50%.

[0185] [Cu: 0~1.000%]

[0186] Cu is an element that can improve the hardenability of steel and stably ensure the strength of the steel plate component after quenching. In addition, Cu improves the pitting resistance in a corrosive environment. In order to fully demonstrate the above effect, it is preferred that the Cu content is set to more than 0.100%. On the other hand, by having a Cu content of less than 1.000%, the above effect can be fully obtained, and the economic efficiency is improved. Therefore, the Cu content in the case of containing Cu is preferably set to less than 1.000%. As required, the Cu content can also be set to less than 0.600%, less than 0.400% or less than 0.200%.

[0187] [Mo: 0-1.00%]

[0188] Mo is an element that can improve the hardenability of steel and stably ensure the strength of the steel plate component after quenching. In order to fully demonstrate the above effect, it is preferred that the Mo content is set to 0.10% or more. On the other hand, by having a Mo content of 1.00% or less, the above effect can be fully obtained, and the economic efficiency is improved. Therefore, the Mo content in the case of containing Mo is preferably set to 1.00% or less. As needed, the Mo content can also be set to 0.60% or less, 0.40% or less, or 0.20% or less.

[0189] [V: 0~1.00%]

[0190] V is an element that can improve the hardenability of steel and stably ensure the strength of the steel plate component after quenching. In order to fully demonstrate the above effect, it is preferred that the V content is set to 0.10% or more. On the other hand, by having a V content of 1.00% or less, the above effect can be fully obtained, and the economy is improved. Therefore, the V content in the case of containing V is preferably set to 1.00% or less. As needed, the V content can also be set to 0.60% or less, 0.40% or less, or 0.20% or less.

[0191] [Nb: 0~1.00%]

[0192] Nb is an element that can improve the hardenability of steel and stably ensure the strength of the steel plate component after quenching. In order to fully demonstrate the above effect, it is preferred to set the Nb content to 0.01% or more. On the other hand, by setting the Nb content to 1.00% or less, the above effect can be fully obtained, and the economic efficiency is improved. Therefore, the Nb content in the case of containing Nb is preferably set to 1.00% or less. As needed, the Nb content can also be set to 0.50% or less, 0.20% or less, or 0.10% or less.

[0193] [Sn: 0~1.00%]

[0194] Sn is an element that improves pitting resistance in a corrosive environment. In order to fully demonstrate the above effect, the Sn content is preferably set to 0.01% or more. On the other hand, by setting the Sn content to 1.00% or less, the reduction in grain boundary strength can be suppressed, and the reduction in toughness can be suppressed. Therefore, the Sn content in the case of containing Sn is preferably set to 1.00% or less. As needed, the Sn content can also be set to 0.40% or less, 0.10% or less, or 0.05% or less.

[0195] [W: 0~1.00%]

[0196] W is an element that can improve the hardenability of steel and stably ensure the strength of steel plate components after quenching. In addition, W improves pitting resistance in a corrosive environment. In order to fully demonstrate the above effect, it is preferred to set the W content to 0.01% or more. On the other hand, by setting the W content to 1.00% or less, the above effect can be fully obtained, and the economic efficiency is improved. Therefore, the W content in the case of containing W is preferably set to 1.00% or less. As needed, the W content can also be set to 0.60% or less, 0.40% or less, or 0.20% or less.

[0197] [Ca: 0~0.010%]

[0198] Ca is an element that has the effect of miniaturizing inclusions in steel and improving toughness and ductility after quenching. In order to fully demonstrate the above effect, it is preferred that the Ca content is set to 0.001% or more, and more preferably to 0.002% or more. On the other hand, by setting the Ca content to 0.010% or less, its effect can be fully obtained and the cost can be suppressed. Therefore, the Ca content in the case of containing Ca is preferably set to 0.010% or less, and more preferably to 0.004% or less. As needed, the Ca content can also be set to 0.008% or less, 0.006% or less, or 0.0004% or less.

[0199] [REM: 0~0.30%]

[0200] REM is an element that has the effect of miniaturizing inclusions in steel and improving toughness and ductility after quenching, just like Ca. In order to fully exhibit the above effect, the REM content is preferably set to 0.001% or more, and more preferably to 0.002% or more. On the other hand, by setting the REM content to 0.30% or less, the effect can be fully obtained and the cost can be suppressed. Therefore, when REM is contained, the REM content is preferably set to 0.30% or less, and more preferably to 0.20% or less. As needed, the Ca content can also be set to 0.10% or less, 0.05% or less, or 0.02% or less.

[0201] Here, REM refers to Sc, Y and lanthanoid elements, a total of 17 elements, and the above REM content refers to the total content of these elements. REM is added to molten steel using, for example, Fe-Si-REM alloy, and the alloy contains, for example, Ce, La, Nd, and Pr.

[0202] The remainder other than the above components is Fe and impurities. In addition to the above components, the base steel plate 11 may also contain impurities mixed in the manufacturing process, etc. within a range that does not hinder the effect of the present invention. Examples of the impurities include Zn (zinc) and Co (cobalt).

[0203] The chemical composition of the base steel plate 11 of the above-mentioned hot stamping aluminum-plated steel plate 10 can be measured by general analytical methods. For example, ICP-AES (Inductively Coupled Plasma-Atomic Emission Spectrometry) can be used for measurement. C and S can be measured using the combustion-infrared absorption method, N can be measured using the inert gas melting-thermal conductivity method, and O can be measured using the inert gas melting-non-dispersive infrared absorption method. In the case where the steel plate for hot stamping has a coating on the surface, the chemical composition can be analyzed by removing the coating on the surface by mechanical grinding.

[0204] The portion of the surface of the plated steel sheet including the base steel sheet 11 having the above-mentioned chemical composition and the aluminum plating layer 12 to which the surface treatment film 13 is applied can be made into a hot stamping component having high tensile strength by heating and quenching using the hot stamping method. In addition, in the hot stamping method, since the pressing process can be performed in a softened state at a high temperature, it can be easily formed.

[0205] (Method for producing aluminum-plated steel sheet for hot stamping)

[0206] An example of a method for manufacturing an aluminum-plated steel sheet for hot stamping according to the present embodiment is described below. It should be noted that the aluminum-plated steel sheet for hot stamping according to the present embodiment only needs to have the above-mentioned structure, and the manufacturing method is not particularly limited. The following manufacturing method is an example for manufacturing an aluminum-plated steel sheet for hot stamping according to the present embodiment, and is a preferred example of a method for manufacturing an aluminum-plated steel sheet for hot stamping according to the present embodiment.

[0207] <Base Steel Plate>

[0208] The base steel sheet for aluminum plating is not particularly limited as long as it can be suitably used in the hot stamping method. Examples of the form of the base steel sheet include steel sheets such as hot-rolled steel sheets and cold-rolled steel sheets.

[0209] <Formation of Aluminum Plating Layer>

[0210] The method for forming the aluminum plating layer may include hot-dip plating, electroplating, physical vapor deposition, chemical vapor deposition, etc., but is not particularly limited. The aluminum plating layer is formed on the surface of the base steel plate by a known method.

[0211] <Method for producing surface-treated film>

[0212] The method for producing the surface treatment film is not particularly limited, but for example, the following method can be cited: each film-forming component is mixed, stirred with a disperser, and the mixed treatment liquid obtained by dissolving or dispersing is applied to the plated layer, and then dried. The mixed treatment liquid is prepared, for example, by adjusting the treatment liquid of compound A and the treatment liquid of compound B respectively, adjusting the pH, and then mixing each treatment liquid with other arbitrary components such as resin.

[0213] The following is a specific description.

[0214] Examples of the compound A contained in the surface treatment film include carbon black, graphite, soot, etc. In the method for producing the surface treatment film, a treatment liquid prepared by dispersing these powders in water or the like is preferably used.

[0215] Compound A is crushed by a machine or the like in a manner such that the powder diameter (particle size) becomes between 30 and 300 nm, and then compound A is put into a treatment solution containing sodium hydroxide and adjusted to a pH of 9.0 to 13.0. Afterwards, the treatment solution into which compound A is put is subjected to a pre-treatment by stirring at 50°C to 80°C for 1 to 4 days, so that compound A with a particle size of 30 to 300 nm can be more stably dispersed in the treatment solution. In addition, when a surface treatment film is formed, compound A can be uniformly present in the film layer, thereby improving the temperature rise characteristics.

[0216] Furthermore, by heating the treatment solution with a pH of 9.0 to 13.0 in which the compound A is added at 50°C to 80°C for 1 to 4 days (i.e., satisfying the above-mentioned pretreatment conditions), the carbon concentration of the compound A in the film can also be increased. If the treatment solution is subjected to this pretreatment, the region with a low carbon concentration outside the particle of the compound A (for example, a portion with a high ratio of oxygen (O), nitrogen (N), sulfur (S), etc.) is dissolved by the treatment solution containing sodium hydroxide, and the region with a high carbon concentration inside the particle remains. Thus, the carbon concentration of the compound A in the film can also be increased.

[0217] On the other hand, when the above-mentioned pretreatment conditions are not met (for example, when the stirring time is less than 1 day, etc.), the amount of dissolution in the region with a low carbon concentration outside the particles of compound A decreases, and the carbon concentration of compound A in the film decreases relatively. Therefore, in order to sufficiently increase the carbon concentration of compound A in the film, it is necessary to control the above-mentioned pretreatment conditions before applying the treatment solution.

[0218] The compound B which is an oxide or fluoride of the metal element M and has a rutile structure is also preferably used in the form of a powder or a treatment liquid dispersed in water or a solvent.

[0219] Compound B is crushed by a machine or the like so that the powder diameter (particle size) becomes between 10 and 300 nm, and then put into a treatment solution containing sodium fluoride and adjusted to pH 3 to 7, and pre-treated by stirring at 50° C. to 80° C. for 4 to 24 hours. Thus, compound B with a particle size of 10 to 300 nm can be more stably dispersed in the treatment solution. As a result, when a surface treatment film is formed, the existence form of compound B as described later can be realized in the film, thereby improving the temperature rise characteristics.

[0220] The surface treatment film of the present embodiment can be obtained by using a mixed treatment liquid obtained by appropriately adding a binder component (resin) to the raw materials and treatment liquid selected in this manner.

[0221] The manufacturing method of the mixed treatment liquid obtained by combining the treatment liquid of compound A with the treatment liquid of compound B is not particularly limited, but for example, the following method can be cited: the treatment liquid containing compound A obtained by the above method is mixed with the treatment liquid containing compound B, stirred with a disperser to dissolve or disperse it, and then a binder (resin) and silicon dioxide are added as needed. In order to improve the solubility or dispersibility of each film-forming component, a known hydrophilic solvent or the like can also be added as needed. In the treatment liquid, an acid, a base, etc. can also be added for pH adjustment within the range that does not damage its performance.

[0222] Hereinafter, the method for producing the mixed treatment liquid will be described in detail.

[0223] In order to achieve a surface treatment film that satisfies the above-mentioned formula (1) and formula (2), first, compound A and compound B are each dispersed in water or a mixed solution of water and a solvent such as ethanol, and each treatment solution is prepared by the above-mentioned adjustment method. After that, the binder component (resin, etc.) is mixed with the treatment solution of compound A, and then the treatment solution of compound B is mixed to prepare a mixed treatment solution. It should be noted that after the treatment solution of compound B with a pH of 3 to 7 is stirred at 30 to 50°C for 4 to 25 hours, before being mixed with the treatment solution of compound A, the treatment solution of compound B is set to a pH of 8 or above using ammonia water or the like. In addition, when silica is contained in the surface treatment film, it is preferable to mix the treatment solution of compound B with the mixed solution and then add silica.

[0224] In order to set the content of compound A at the interface side position P of the surface treatment film to 30% or more, the concentration (content) of compound A in the mixed treatment liquid is set to 15% by mass or more in terms of dry weight (mass) ratio. In order to set the content of compound A at the interface side position P of the surface treatment film to 80% or less, the concentration (content) of compound A in the mixed treatment liquid is set to 50% by mass or less in terms of dry weight (mass) ratio.

[0225] In order to satisfy the equations (1) and (2) regarding the concentration of the metal element M, the concentration (content) of the compound B in the mixed treatment liquid is set to 3 to 50 mass % in terms of dry weight (mass) ratio.

[0226] The total of the concentration (content) of the compound A and the concentration (content) of the compound B in the mixed treatment liquid is set to 18 to 90% in terms of dry weight (mass) ratio.

[0227] Next, it is preferred that the obtained mixed treatment liquid is stirred at 150 rpm to 300 rpm immediately before coating, and the stirred mixed treatment liquid is coated within 5 seconds.

[0228] In order to achieve a surface treatment film that satisfies the above-mentioned formula (1) and formula (2), the shear rate is set to 10 -3 The dynamic viscosity of the mixed treatment liquid at 1000 Å / s is set to 3 to 16 mPa·s, and the surface tension is set to 20 to 60 mN / m.

[0229] When the dynamic viscosity is lower than 3 mPa·s, it is possible to bM / C tM If the dynamic viscosity exceeds 10.0, the desired temperature rise rate cannot be obtained. Therefore, the dynamic viscosity of the mixed treatment liquid is set to be 3 mPa·s or more, preferably 6 mPa·s or more. On the other hand, if the dynamic viscosity exceeds 16 mPa·s, it is possible that C in formula (2)bM / C tM If the ratio is less than 1.5, the desired temperature increase rate cannot be obtained. Therefore, the dynamic viscosity of the mixed treatment liquid is set to 16 mPa·s or less, preferably 12 mPa·s or less.

[0230] In addition, when the surface tension of the mixed treatment liquid is lower than 20 mN / m, C bM When the surface tension is lower than 1 mass %, the desired heating rate cannot be obtained. Therefore, the surface tension of the mixed treatment liquid is set to be 20 mN / m or more, preferably 30 mN / m or more. On the other hand, when the surface tension exceeds 60 mN / m, the desired heating rate cannot be obtained. Therefore, the surface tension of the mixed treatment liquid is set to be 60 mN / m or less, preferably 40 mN / m or less.

[0231] To form the surface treatment film layer, the treatment liquid is applied on the aluminum plating layer (or chemical conversion treatment layer), and the coating film is heated and dried. The coating method of the treatment liquid is not particularly limited, and it can be a generally known coating method, such as a method using roll coating, dipping, etc.

[0232] In order to control compound B to have a predetermined concentration distribution as shown in formula (1) and formula (2), the heating and drying temperature after coating is set to a final temperature of 55° C. to 120° C. It should be noted that the “final temperature” here refers to the temperature of the surface of the base steel plate.

[0233] When the reaching temperature is lower than 55°C, the evaporation rate of water is slow and sufficient film forming properties cannot be obtained, so there is a possibility that the film adhesion is insufficient. Furthermore, when the reaching temperature is too low, the evaporation rate of the treatment liquid is slow, so the metal element M in the compound B is concentrated on the Al plating layer side, and C bM / C tM If the temperature reaches 120°C, the adhesive component may be modified due to thermal decomposition, and the adhesion and corrosion resistance may be reduced. The temperature is more preferably 65 to 100°C.

[0234] In addition, when the time for the temperature of the base steel plate surface to reach 65°C from 25°C is set as t1 (the final temperature of the base steel if it does not reach 65°C), and the time until the temperature is reduced from 65°C (or the final temperature of the base steel) to 40°C by cooling is set as t2, t1 is set to 1.5 seconds to 14.0 seconds, t2 is set to 0.5 seconds to 8.6 seconds, and t1 / t2 is set to a range of 0.35 to 10.0. Thus, it becomes easy to control the concentration distribution C in the surface treatment film of compound B. bM / CtM , the heating rate is further improved.

[0235] Furthermore, when the time for the temperature of the base steel plate surface to reach 55° C. from 25° C. is set as t3, t3 is set to 5.0 seconds to 12.0 seconds. Thus, the content of compound A at the interface side position P can be set to 30 to 80%.

[0236] The method for heating and drying the applied treatment liquid is not particularly limited, and examples thereof include methods using hot air, induction heating, near infrared rays, direct flame, etc., alone or in combination. As components of the treatment liquid for dispersing or dissolving the resin, water or a solvent can be used.

[0237] (Method for manufacturing hot stamped component)

[0238] Various hot stamping parts such as those exemplified in the automobile frame parts can be produced using an aluminum-plated steel sheet for hot stamping to which the above-mentioned surface treatment film is applied over the entire surface of at least one surface.

[0239] First, for example, the aluminum-plated steel sheet to which the surface treatment film is applied is subjected to various processing such as cutting and pressing to punch out, thereby obtaining the aluminum-plated steel sheet for hot stamping according to the present embodiment.

[0240] In addition, the hot stamping aluminum-plated steel sheet of the present embodiment can be obtained by applying a surface treatment film to the aluminum-plated steel sheet that has been punched out by cutting, pressing, etc. In addition, by partially reducing the film thickness of the surface treatment film, it becomes easy to conduct electricity in the application of welding multiple steel sheets before hot stamping, and the spot weldability can be improved.

[0241] The hot stamping aluminum-plated steel sheet to which the surface treatment film is applied is hot stamped as described above. As a heating device, for example, there are an electric heating furnace, a gas heating furnace, a far-infrared furnace, a common heating device with an infrared heater, and the like. The surface on one side to which the emissivity is increased by applying the surface treatment film has a large heat transfer effect generated by radiation, so the heating rate is fast. Therefore, the temperature can be quickly raised to a temperature above the Ac3 point at which the metal structure is transformed into the austenite phase. Thus, in the manufacturing method of the hot stamping component of the present embodiment, by seeking to shorten the heating time, the productivity of the hot stamping component can be further improved. In the present embodiment, there is no particular limitation on the specific heating conditions, as long as the heating device used is appropriately controlled.

[0242] Next, the heated steel sheet is formed and cooled. The portion heated to a temperature above the Ac3 point, at which the metal structure of the steel material is transformed into an austenite phase, is quenched while being formed, thereby increasing the strength. Thus, a hot stamping component with increased strength can be obtained.

[0243] Example

[0244] The following describes an embodiment of the present invention, but the conditions in the embodiment are only a condition example adopted to confirm the feasibility and effect of the present invention, and the present invention is not limited to this condition example. As long as it does not deviate from the gist of the present invention and achieves the purpose of the present invention, the present invention can adopt various conditions.

[0245] As the base steel plate, a steel plate having high mechanical strength (referring to various properties related to mechanical deformation and destruction such as tensile strength, yield point, elongation, drawing depth, hardness, impact value, fatigue strength, etc.) is preferably used.

[0246] The chemical components of the base steel sheets before plating used in the hot stamping steel sheets described in the following Examples are shown in Table 1 below.

[0247] [Table 1]

[0248]

[0249] For the base steel plates (steel No. S1 to S10) having the chemical composition shown in Table 1, a steel plate (base steel plate) having a width of 100 mm × a length of 200 mm and a plate thickness of 2.3 mm was prepared, and an aluminum plating layer and a surface treatment film were applied to the entire surface of both sides of the base steel plate by the method described below. Here, the expression "-" in Table 1 means that the corresponding element content is 0% in the significant figure (the value to the minimum digit) specified in this embodiment.

[0250] First, an aqueous treatment liquid (solvent: water) to which at least one of carbon black (CB), graphite, and soot powdered in a manner to have a powder diameter (particle size) between 30 and 300 nm is added as compound A, and an aqueous treatment liquid (solvent: water) to which a metal oxide or metal fluoride powdered in a manner to have a powder diameter (particle size) between 30 and 300 nm is added as compound B. Then, each treatment liquid is mixed, and a polyurethane resin is further added to obtain a treatment liquid, which is applied to the aluminum plating layer and dried to form a surface treatment film. The film thickness of the surface treatment film is set within the range of 1.0 to 2.5 μm, and the same film is applied to both sides.

[0251] Tables 2A and 2B describe the methods for producing surface treatment films such as the types of compounds and additives used. In all the production methods in Tables 2A and 2B, polyurethane resin is added in a manner such that the ratio in the solid content in the treatment liquid is 10 to 92% by mass. In addition, in all the production methods in Tables 2A and 2B, sodium fluoride is used as an additive when adjusting compound B. In addition, when the treatment liquids of compound A and compound B are mixed, they are adjusted in a manner such that the dry weight ratio is as shown in Tables 2A and 2B. It should be noted that the underline in Tables 2A and 2B indicates the preferred conditions that deviate from the production method of the present invention.

[0252] The dynamic viscosity (mPa·s) shown in Table 2A and Table 2B is the value when the shear rate is 10 -3 The "time t1", "time t2" and "time t3" shown in Table 2A and Table 2B respectively represent "the time for the temperature of the base steel plate surface to reach 65°C from 25°C", "the time for the temperature of the base steel plate surface to decrease from 65°C to 40°C", and "the time for the temperature of the base steel plate surface to reach 55°C from 25°C".

[0253] [Table 2A]

[0254]

[0255] [Table 2B]

[0256]

[0257] After that, a thermocouple was connected to the surface of the aluminum-plated steel sheet (HS aluminum-plated steel sheet) with a surface treatment film, so that the temperature at each position could be measured. Then, the HS aluminum-plated steel sheet was heated in an electric heating furnace set at 940°C, and when the surface temperature reached 930°C, the HS aluminum-plated steel sheet was taken out of the heating furnace. After that, the HS aluminum-plated steel sheet was rapidly cooled with a flat die to obtain a hot stamping component.

[0258] It should be noted that in this embodiment, the Al-10 mass % Si coating is applied to the base steel plate by hot dip coating, and the above-mentioned surface treatment film is applied thereto. In the case of hot dip coating, the base steel plate is immersed in the coating bath, and then the coating weight is adjusted to 100 g / m per single side by gas wiping. 2 .

[0259] The film composition, heating rate (heating characteristics) and film adhesion of the surface treatment film were investigated. It should be noted that hot stamping components are not necessarily used as components subject to sliding, etc. Therefore, in this embodiment, film adhesion is not a necessary characteristic that hot stamping components should have, but a preferred characteristic.

[0260] The evaluation method of each evaluation item is set as follows.

[0261] (1) Heating rate (heating characteristics)

[0262] (score)

[0263] The temperature rise rate in each HS aluminum-plated steel sheet was calculated and evaluated based on the temperature change obtained by the thermocouple installed on each HS aluminum-plated steel sheet and the heating time in the electric heating furnace. Specifically, the temperature rise rate from room temperature to 910°C was calculated and evaluated based on the following evaluation criteria. A score of "2" or above was set as passing.

[0264] (score)

[0265] 4: Heating rate is above 5.7℃ / s

[0266] 3: The heating rate is above 4.3℃ / s and below 5.7℃ / s

[0267] 2: The heating rate is above 3.5℃ / s and below 4.3℃ / s

[0268] 1: Heating rate is lower than 2.5℃ / s

[0269] (2) Membrane adhesion

[0270] The obtained hot stamped body was placed in a friction tester ("Rubbing Tester 1509" manufactured by Imoto Seisakusho Co., Ltd.), and evaluated according to the following evaluation criteria: a stroke distance of 100 mm, a speed of 30 reciprocations per minute, and a load of 0.5 kgf / cm 2 The state of the film after sliding (reciprocating) 10 times.

[0271] (score)

[0272] 3: There is absolutely no trace in the entire sliding portion.

[0273] 2: There is a slight mark on a part of the sliding portion.

[0274] 1: The epithelial film disappears in the sliding part.

[0275] <Example 1>

[0276] In Table 3, B1 to B16 are invention examples, and b1 to b8 are comparative examples.

[0277] In this example, when preparing the aqueous treatment liquid, carbon black (CB), graphite, and soot powder and aqueous dispersion were used as compounds other than the binder component.

[0278] In comparative example b1, the carbon concentration of compound A is as low as 71%. In comparative examples b2 to b4, compound B is not a rutile structure. In comparative examples b5 and b10, formula (1) is not satisfied. In comparative examples b6, b7, b8, and b9, formula (2) is not satisfied. In comparative examples b1 to b7, b9, and b10, the heating rate is scored as 1, whereas in inventive examples B1 to B16, the heating rate is scored as 2.

[0279] [Table 3]

[0280]

[0281] <Example 2>

[0282] As shown in Table 4, inventive examples C2 to C11 having a content of 30 to 80% of compound A at a position 0.90H from the surface of the surface treatment film (i.e., interface side position P) have a better heating rate than C1 having a content of 20% of compound A at the same position.

[0283] [Table 4]

[0284]

[0285] <Example 3>

[0286] As shown in Table 5, the temperature rise rates of Invention Examples D6 to D9 in which Compound B is TiO 2 are superior to those of Invention Examples D1 and D5 in which Compound B is IrO 2 or GeO 2 .

[0287] [Table 5]

[0288]

[0289] The preferred embodiments of the present invention are described in detail above, but the present invention is not limited to the examples. Anyone with ordinary knowledge in the technical field to which the present invention belongs can obviously think of various variations or modifications within the scope of the technical ideas recorded in the claims, and these are of course understood to belong to the technical scope of the present invention.

[0290] Industrial Applicability

[0291] According to the above aspect of the present invention, an aluminum-plated steel sheet for hot stamping that can further improve the productivity of hot stamped parts can be provided, and therefore the industrial applicability is high.

[0292] Explanation of symbols

[0293] 10Aluminum-coated steel sheet for hot stamping

[0294] 11 Base steel plate

[0295] 12 Aluminum coating

[0296] 13 Surface treatment film

[0297] 14 Base treatment film

Claims

1. An aluminum-plated steel sheet for hot stamping, characterized in that: have: Base steel plate; An aluminum plating layer having an Al content of 80 mass % or more provided on at least one surface of the base steel plate; and A surface treatment film is provided on the aluminum plating layer, Wherein, the surface treatment film contains: a compound A comprising carbon; and A compound B which is an oxide or fluoride of a metal element M and has a rutile structure, The carbon concentration of the compound A is 80% by mass or more, The concentration of the metal element M satisfies the following formula (1) and the following formula (2): 1≤C bM ≤40 Formula (1) 1.5≤C bM / C tM ≤10.0 Formula (2) When the average thickness of the surface treatment film is set to H, C in the formula (2) is tM is the concentration of the metal element M at a position 0.05H from the surface of the surface treatment film in mass %, In the formula (1) and the formula (2), C bM It is the concentration of the metal element M at a position 0.95H from the surface of the surface treatment film in mass %.

2. The aluminum-plated steel sheet for hot stamping according to claim 1, characterized in that: The content of the compound A is 30 to 80% at a position 0.90H from the surface of the surface treatment film.

3. The aluminum-plated steel sheet for hot stamping according to claim 1 or 2, characterized in that: The compound B is TiO2.

Citation Information

Patent Citations

  • Hot press formed product with high corrosion resistance

    JP2003126921A

  • Al PLATED STEEL SHEET FOR HOT PRESS HAVING EXCELLENT TEMPERATURE RISING PROPERTY, AND METHOD FOR PRODUCING THE SAME

    JP2011149084A

  • Method for manufacturing press hardened and coated steel parts at high production rates

    JP2017518438A

  • Cement admixture and cement composition

    JP2022135751A